1999
DOI: 10.1080/095530099140717
|View full text |Cite
|
Sign up to set email alerts
|

Heat sensitivity of double-stranded DNA-dependent protein kinase (DNA-PK) activity

Abstract: DNA-PK was inactivated by heat treatment at 44 degrees C. Ku70/Ku80, but not Ku70 alone, could restore heat-inactivated DNA-PK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…1) Matsumoto et al, 1997;Beck and Dynlacht, 2001). Several investigators have demonstrated that Ku80 loses its activity rapidly after cells are heated, and may be the heat-sensitive component of DNA-PK (Ihara et al, 1999). Despite evidence that the protein becomes altered and loses its activity after heat shock, thus implicating it as a target for heat-inhibition of DSB repair, a role in heat-radiosensitization has yet to be conclusively demonstrated.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…1) Matsumoto et al, 1997;Beck and Dynlacht, 2001). Several investigators have demonstrated that Ku80 loses its activity rapidly after cells are heated, and may be the heat-sensitive component of DNA-PK (Ihara et al, 1999). Despite evidence that the protein becomes altered and loses its activity after heat shock, thus implicating it as a target for heat-inhibition of DSB repair, a role in heat-radiosensitization has yet to be conclusively demonstrated.…”
Section: Discussionmentioning
confidence: 97%
“…It is believed that such alterations result in a binding of the proteins to DNA or the nuclear matrix, resulting in a masking of sites of radiation-induced DNA damage, or a reduction in accessibility of repair proteins to sites of DSBs (Roti Roti and Winward, 1978;Tomasovic et al, 1978;Warters et al, 1987;Warters et al, 1993;Roti Roti et al, 1997). Conversely, studies on DNA polymerases and more recent studies involving DSB repair proteins suggest that denaturation or aggregation may directly result in inactivation or decreased functionality of the DNA repair enzymes themselves that are responsible for DSB repair (Spiro et al, 1982;Jorritsma et al, 1985;Kampinga et al, , 1993Raaphorst et al, 1993;Burgman et al, 1997;Matsumoto et al, 1997;Ihara et al, 1999). Recent results from cell-free studies performed by Wachsberger and Iliakis (2000) also argue against a role for reduction in accessibility of repair proteins in heat-inhibition of DSB repair.…”
mentioning
confidence: 92%
“…To this purpose, we studied the DNA repair machinery activation induced by ICG photoactivation at 810 nm. To define the nature of cell damage, the activation of Ku70 and Ku80 heterodimer subunits was observed because their expression is involved in the regulation of cell death induction and inhibited by heat shock [23][24][25] . Moreover, the activation of the proapoptotic pathway after damage induced by ICG photosensitization at 810 nm was observed.…”
mentioning
confidence: 99%
“…Several lines of evidence show that factors involved in DSB repair are likely to be affected by heat shock, for example, Ku heterodimer (Ku70/Ku80) [33][34][35][36], MRN complex [37][38][39], breast cancer susceptibility gene 1 (BRCA1) [40], BRCA2 [41] and RAD51 [41,42]. Heat shock affects these proteins by causing denaturation, cytoplasmic translocation from the nucleus, and protein degradation by the proteasome pathway [43].…”
Section: Discussionmentioning
confidence: 99%